ANALISIS YURIDIS KEBIJAKAN PENGELOLAAN PENERIMAAN NEGARA BUKAN PAJAK TERPUSAT DARI KEGIATAN PELAYANAN PERTANAHAN PADA KANTOR PERTANAHAN KOTA SURATARTA - SULISTIYANINGSIH, SULISTIYANINGSIH (Dinamika Hukum, 2018)
Non-Tax State Revenue is one source of state revenues whose current existence becomes increasingly important. This is because the tax revenue in the last few years did not reach the maximum target. Therefore, the optimization of Non-Tax State Revenue is absolutely necessary. The Legal Basis used by the Ministry of Agrarian Affairs and the National Land Administration in collecting Non-Tax State Revenues (PNBP) is Law No. 20/1997 on Non-Tax State Revenues whereas the types and tariffs have been amended several times and the last amended by Government regulation No. 128 Year 2015. In general the realization of Non-Tax State Revenue and the National Land Agency / Land Agency continues to increase means that there is a continuous increase Non-Tax State Revenue At the Ministry of Agrarian Affairs and Spatial / National Land Agency. Not aligned realisasai target Non-Tax State Revenue with the realization of the use of budgets sourced from Non-Tax State Revenue indicates that there are obstacles in the management of Non-Tax State Revenues in the Ministry of Agrarian Affairs and the National Land Office / Land Agency which will affect the performance of service performance. Method This research is a type of empirical research with the nature of deskrptif is to describe how the management of Non-Tax State Revenue from Land Service Activity at the Land Office of Surakarta and the obstacles experienced in the management of Non-Tax State Revenue. The results of the research indicate that the management of Non-Tax State Revenues before 2016 with the system Not centralized, depositing, recording bookkeeping and reporting implemented by each Unit / office and the use of PNBP funds can only be enjoyed Producer Unit and used directly by the work unit according to the permit use . At the time of disbursement of funds must enclose evidence of Non Tax Payment (SSBP) that has been confirmed or validated by the Office of State Treasury Services. After 2016 with centralized management, direct deposit to the Secretariat General of the Ministry of Agrarian Affairs and Spatial / BPN with the application of SIMPONI is integrated with the CTF WEB and its use is based on the Maximum Disbursement from the Director General of Treasury without attaching the Non-Tax Payment Letter. Keywords: Budget Management, Centralized PNBP